Institutional Model Design for the Implementation of the Program Merdeka Belajar Kampus Merdeka (Merdeka Learning Program-Merdeka Campus or MBKM) - Defrizal; Appin Purisky Redaputri; Vonny Tiara Narundana; Nurdiawansyah; Yanuarius Yanu Dharmawan (Indonesia Approach Education, 2022)
MBKM program has been implemented by several universities, including at the Universitas Bandar Lampung. Universities need to determine policies that serve as guidelines for the study programs they cover, including support for cross-study learning and allocation of funds, as well as ensuring that the quality of graduates will not decrease by running this program. For this reason, in its implementation, it is necessary to form an institutional model for the implementation of Merdeka Learning Program - Merdeka Campus to see who has a role and how the relationship between these parties plays a role. This research uses a descriptive qualitative approach. In collecting the data, it applies literature studies and In-Depth Interviews with resource persons who are experts related to the Merdeka Learning Program - Merdeka Campus. The results in this study found that in the implementation of the Merdeka Learning Program - Merdeka Campus at the Universitas Bandar Lampung, there were internal and external stakeholders involved. Each stakeholder has its respective roles and relationships, both coordination and command relationships, both between internal stakeholders and between internal and external stakeholders. Everything is described in the institutional model of the Merdeka Learning Program - Merdeka Campus.